Conceptualizing and measuring father involvement - Day, Randal D., 1948-; Lamb, Michael E., 1953- (Lawrence Erlbaum Assoc. Pub., 2004)
This comprehensive study focuses on ways of measuring the efficacy of father involvement in different scenarios, using different methods of assessment and different populations. It stems from a series of workshops and publications sponsored by the Family and Child Well-Being Network.